PERBUATAN MELAWAN HUKUM (ONRECHTMATIGE DAAD) ATAS JASA PELAYANAN MEDIS (Studi Putusan Mahkamah Agung Nomor 1001.K/Pdt /2017) - Salma Fadillah; Benni Rusli (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Supreme Court Decision No. 1001.K/Pdt/2017 is the plaintiff's cassation against the defendants who providing medical services at the MMC Hospital. As a result of the actions of the plaintiffs, the plaintiff's wife died while Caesar operation finish. The focus of the problem, the Judge canceled the Appeal Decision and also canceled the South Jakarta District Court Decision. The Supreme Court judge chose to conduct a separate trial of the case material. The Supreme Court judge decided to try that the plaintiffs were declared to have committed an unlawful act. Formulation of the problem 1) How is the act against the law (onrechtmatige daad) for medical services? 2) What are the considerations of the judges in deciding on unlawful acts (onrechtmatige daad) for medical services? Descriptive research, using a normative juridical approach. After studying the documents, the research resulted in conclusions 1) The Supreme Court judge in the PMH trial for medical services overturned the decision at the first level court and the second level court decision. The judge assessed the lawsuit material, looked at the evidence and then decided to try the case that the defendants had committed an unlawful act and had to pay compensation in the amount of 1,000,000,000.- (One Billion Rupiah). 2) The judge's considerations in the Supreme Court Decision, basically considers the matter of the case. The judge considered that the PMH elements had already existed when Defendant I convinced the plaintiff's wife to become pregnant and undergo a caesarean section for the fourth time. Defendant I did not explain how dangerous this action was for the plaintiff's wife, including the possibility of the plaintiff's wife dying.